2019
DOI: 10.3389/fnagi.2019.00307
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Disruptive Patterns of Default Mode Subnetwork Connectivity Across the Spectrum of Preclinical Alzheimer’s Disease

Abstract: Background: The early progression continuum of Alzheimer’s disease (AD) has been considered to advance through subjective cognitive decline (SCD), non-amnestic mild cognitive impairment (naMCI), and amnestic mild cognitive impairment (aMCI). Altered functional connectivity (FC) in the default mode network (DMN) is regarded as a hallmark of AD. Furthermore, the DMN can be divided into two subnetworks, the anterior and posterior subnetworks. However, little is known about distinct disruptive patterns in the subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
65
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 59 publications
4
65
1
Order By: Relevance
“…Hence, the altered regions we found might involve in language cognitive disorder, and pDMN first appears abnormal connections compared to aDMN, which might suggest that the aDMN and pDMN have different manifestations in the early stages of AD. We found that both aMCI and SCD groups showed a prominent region in SFG that is connected to DMN subnetworks, and according to the previous research that the altered functional connectivity between the pDMN and the SFG might be a compensatory response of brain (Xue et al, 2019). We assume that the aberrant PPC in SFG connected to the DMN may also be caused by the brain's compensation.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Hence, the altered regions we found might involve in language cognitive disorder, and pDMN first appears abnormal connections compared to aDMN, which might suggest that the aDMN and pDMN have different manifestations in the early stages of AD. We found that both aMCI and SCD groups showed a prominent region in SFG that is connected to DMN subnetworks, and according to the previous research that the altered functional connectivity between the pDMN and the SFG might be a compensatory response of brain (Xue et al, 2019). We assume that the aberrant PPC in SFG connected to the DMN may also be caused by the brain's compensation.…”
Section: Discussionsupporting
confidence: 74%
“…Interestingly, compared to patients with SCD, DMN subnetworks in aMCI group showed obvious differences in right SFGMP and left MFGOP belonging to FG. In previous studies, aMCI group showed more widespread topological changes involving the frontal lobes (Barban et al, 2017), and aberrant connectivity was also found in patients with SCD between DMN and FG due to cognitive impairment (Xue et al, 2019). Besides, an increasing trend of values of amplitude of low-frequency fluctuation (ALFF) and fractional ALFF were detected in FG (Yang et al, 2018).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Previous study has identified that the non-parametric permutation test with Threshold-Free Cluster Enhancement (TFCE) can strike a good and strict balance between familywise error rate and reliability . Consequently, permutation tests with TFCE, implemented in PLAM within DPABI, were utilized to perform multiple comparisons in this work, and then a cluster size > 10 voxels (270 mm 3 ) was adopted as the significant cluster, and the significance level was set at 0.05 (Xue C. et al, 2019).…”
Section: Discussionmentioning
confidence: 99%